2006
DOI: 10.1093/ps/85.9.1541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Grains Naturally Contaminated with Fusarium Mycotoxins on Performance and Metabolism of Broiler Breeders

Abstract: A study was conducted to investigate the effects of feeding grains naturally contaminated with Fusarium mycotoxins on performance and metabolism of broiler breeders. Forty-two 26-wk-old broiler breeder hens and nine 26-wk-old roosters were fed the following diets: (1) control, (2) contaminated grains, and (3) contaminated grains + 0.2% polymeric glucomannan mycotoxin adsorbent (GMA) for 12 wk. The major contaminant was deoxynivalenol (12.6 mg/kg of feed), with lesser amounts of zearalenone and 15-acetyl-deoxyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…It was also observed decrease in STP and albumin [25]. Other workers like [17] and [26] also observed that T-2 toxin caused reduction in STP; however, [27], in contrast, reported no change in STP in breeder hens fed with a mixture of T-2 and other Fusarium toxins. The hypoproteinemia might be due to inhibition of protein synthesis [28][29][30] and is indirect indication of reduced immunoglobulin levels and other immune response factors like cytokines which are protein in nature and thus leading to some degree of immunosuppression in toxicated birds.…”
Section: Discussionmentioning
confidence: 89%
“…It was also observed decrease in STP and albumin [25]. Other workers like [17] and [26] also observed that T-2 toxin caused reduction in STP; however, [27], in contrast, reported no change in STP in breeder hens fed with a mixture of T-2 and other Fusarium toxins. The hypoproteinemia might be due to inhibition of protein synthesis [28][29][30] and is indirect indication of reduced immunoglobulin levels and other immune response factors like cytokines which are protein in nature and thus leading to some degree of immunosuppression in toxicated birds.…”
Section: Discussionmentioning
confidence: 89%
“…A possible explanation for this effect might be the regression of bursa of Fabrisius due to the aflatoxin contamination. In a study, anti-NDV titre was not affected by feeding naturally contaminated diets (12.6 DON and 0.6 mg/kg zearalenone) to fusarium mycotoxins in broiler chickens (Yegani et al 2006). Inversely, Li et al (2012) indicated the reduction in anti-NDV titre of chickens fed diets contaminated with mycotoxins.…”
Section: Treatmentsmentioning
confidence: 98%
“…Sypecka et al (2004), reported that only trace amounts of Fusarium mycotoxins are transferred into the eggs of laying hens, which are unlikely to be of significance with respect to embryonic mortality. Yegani et al (2006) reported no effect in feed consumption, body weight, and egg production. However, increase in early embryonic mortality (1 to 7d) in eggs from birds fed contaminated grains with deoxynivalenol (12.60mg/kg of feed) was observed in broiler breeder hens.…”
Section: Aflatoxicosis In Breedersmentioning
confidence: 93%